Organizational team building culture among teachers in Gombak Selangor - Ab. Samad, Rahmad Sukor; Md. Yassin @ A. Bakar, Adilah (2007)
This study examined the organizational team building culture among teachers in Gombak, Selangor. Aspects that were being studied were the teachers’ perception on the elements of team building, the relation between team building factors and motivational factors and differences between gender and the eight factors of team building which were goals, priorities, roles and responsibilities, self-awareness, leadership, group dynamics, communications and environment. The study employed a survey method for collecting data from 100 purposively selected teachers from 10 government aided secondary schools.